The Influence of Career Planning, Adversity Quotient and Social Support on The Work Readiness of Undergraduate Students of The Faculty of Economics and Business, University of Riau, Class of 2021 - Ciansi Deby Angraini; Kurniawaty Fitri; Mida Aprilina Tarigan (West Science Business and Management, 2025)
Undergraduates in the Class of 2021 from the University of Riau's Faculty of Economics and Business will have their job preparedness assessed in relation to their adversity quotient, social support, and career planning.  This study takes a quantitative approach and uses the entire class of 613 students from the Economics and Business Faculty in 2021 as its population.  There were 242 responders since the sample was selected using a proportionate stratified random sampling method.  Descriptive statistics, tests for data quality, tests for classical assumptions, multiple linear regression analysis, and the coefficient of determination were used to analyze the data, with a significance threshold of 0.05 imposed.  The SPSS version 25 was used for data processing.  Students' job preparation is positively and significantly affected, partially and concurrently, by career planning, adversity quotient, and social support, according to this study's conclusions.  These three independent variables account for 65.5% of the total variance in the dependent variable (R²), with the remaining 34.5 % being impacted by factors beyond the scope of this investigation.